The gut lactic acid bacteria metabolite, 10-oxo-cis-6,trans-11-octadecadienoic acid, suppresses inflammatory bowel disease in mice by modulating the NRF2 pathway and GPCR-signaling - Ando, Miki; Nagata, Kazuki; Takeshita, Ryuki; Ito, Naoto; Noguchi, Sakura; Minamikawa, Natsuki; Kodama, Naoki; Yamamoto, Asuka; Yashiro, Takuya; Hachisu, Masakazu; Ichihara, Gaku; Kishino, Shigenobu; et al. (Frontiers in Immunology, 2024)
Various gut bacteria, including Lactobacillus plantarum, possess several enzymes that produce hydroxy fatty acids (FAs), oxo FAs, conjugated FAs, and partially saturated FAs from polyunsaturated FAs as secondary metabolites. Among these derivatives, we identified 10-oxo-cis-6,trans-11-octadecadienoic acid (γKetoC), a γ-linolenic acid (GLA)-derived enon FA, as the most effective immunomodulator, which inhibited the antigen-induced immunoactivation and LPS-induced production of inflammatory cytokines. The treatment with γKetoC significantly suppressed proliferation of CD4+ T cells, LPS-induced activation of bone marrow-derived dendritic cells (BMDCs), and LPS-induced IL-6 release from peritoneal cells, splenocytes, and CD11c+ cells isolated from the spleen. γKetoC also inhibited the release of inflammatory cytokines from BMDCs stimulated with poly-I:C, R-848, or CpG. Further in vitro experiments using an agonist of GPR40/120 suggested the involvement of these GPCRs in the effects of γKetoC on DCs. We also found that γKetoC stimulated the NRF2 pathway in DCs, and the suppressive effects of γKetoC and agonist of GPR40/120 on the release of IL-6 and IL-12 were reduced in Nrf2-/- BMDCs. We evaluated the role of NRF2 in the anti-inflammatory effects of γKetoC in a dextran sodium sulfate-induced colitis model. The oral administration of γKetoC significantly reduced body weight loss, improved stool scores, and attenuated atrophy of the colon, in wild-type C57BL/6 and Nrf2+/- mice with colitis. In contrast, the pathology of colitis was deteriorated in Nrf2-/- mice even with the administration of γKetoC. Collectively, the present results demonstrated the involvement of the NRF2 pathway and GPCRs in γKetoC-mediated anti-inflammatory responses.